Presence of diadenosine polyphosphates in human tears - Pintor, Jesús; Carracedo, Gonzalo; Alonso, Carmen M.; Bautista, Alfredo; Peral, Assumpta (Pflügers Archiv, 2002)
Diadenosine polyphosphates are naturally occurring substances that facilitate tear secretion. The occurrence of these dinucleotides in human tears has been established and quantified by an HPLC technique and phosphodiesterase treatment. The concentration of these compounds found in tears was 2.0+/-2.2 nM for diadenosine triphosphate (Ap3A), 108.0+/-18.3 nM for diadenosine tetraphosphate (Ap4A) and 37.0+/-6.2 nM for diadenosine pentaphosphate (Ap5A). When subjects were treated with topical ocular anaesthesia, the concentrations of Ap3A, Ap4A and Ap5A changed to 1.5+/-1.7 nM, 189.3+/-19.5 nM and 112.6+/-12.3 nM, respectively. Ap4A and Ap5A increased tear secretion in rabbits, the effect presenting an EC50 value of 19.0+/-1.2 ng/microl and 11.4+/-1.3 ng/microl respectively. In conclusion, diadenosine polyphosphates are released from the corneal epithelium, they stimulate tear production and therefore they may be considered as physiological modulators of tear secretion.